A Biodegradable Glue for Annulus Closure: Evaluation of Strength and Endurance. Issue 9 (1st May 2015) - Vergroesen, Pieter-Paul A.; Bochyn´ska, Agnieszka I.; Emanuel, Kaj S.; Sharifi, Shahriar; Kingma, Idsart; Grijpma, Dirk W.; Smit, Theodoor H.
Abstract : Study Design: A biodegradable glue was biomechanically tested for annulus closure using nondegenerated goat intervertebral discs. Ultimate strength and endurance tests were performed using native and punctured discs as positive and negative controls, respectively. Objective: The aim of this study was to investigate the feasibility and biomechanical properties of a biodegradable glue for annulus closure. Summary of Background Data: There is an unmet clinical need for annulus closure techniques. Isocyanate-terminated tissue glues show potential because they adhere to annulus tissue, have an elastic modulus similar to the annulus, and show limited cytotoxicity to human annulus fibrosus cells. Methods: Three biomechanical tests were performed divided in 2 parts: part 1: ultimate strength tests comparing native, punctured (2.4-mm needle), and glued caprine intervertebral discs (n = 11 per group); part 2: 10 discs per group were subjected to a 10-day ex vivo endurance test of 864, 000 load cycles, followed by ultimate strength tests. Outcome parameters include the restoration of strength after puncture, reduction of herniation in the endurance test, and conservation of glue strength after endurance testing. Results: Part 1: The glue partially restored subsidence to failure and yield strength/ultimate strength ratio of intervertebral discs. Part 2: During endurance testing, 40% of punctured discs failed compared with none of the glued discs. Endurance testing did not affect glue strength, and pooling of ultimate strength tests showed that the glue restored ultimate strength, work to failure, and yield strength/ultimate strength to 79%, 75%, and 119% of native values, respectively. Conclusion: A biodegradable isocyanate-terminated glue increases the force at which nucleus protrusion occurs, and it limits herniations during endurance or ultimate strength tests. Biomechanical tests in a bioreactor provide a low-cost assessment for annulus repair strategies; however, the clinical efficacy needs to be further addressed using long-term in vivo studies. Level of Evidence: N/A Abstract : Supplemental Digital Content is Available in the Text.The strength and endurance of a biodegradable glue for annulus fibrosus closure were tested using punctured goat intervertebral discs. The glue restored the ultimate strength to 79% of native, nonpunctured discs and limited the number of nucleus herniations during 864, 000 load cycles and ultimate failure loading.